Complexes of species of Eumorpha Hübner [1807] (Lepidoptera: Sphingidae) from the Maranhão State, Brazil - Lima, Tauanny Maria Almeida; Sena, Jasmine Déa Nogueira; Câmara, Joseleide Teixeira; Teston, José Augusto (Zootaxa, 2023)
Eumorpha is a genus of moths that was described by Hübner in 1807, and currently has 28 valid species, distributed between temperate and tropical regions of the Americas. Thirteen species have been recorded for Brazil. The main characteristic of the group is the presence of a dark rectangular bar on the forewing of most species and also a pair of triangular spots on the thorax. Maranhão is a Brazilian State located in the Northeast of the country, its territory is composed of three biomes: Cerrado (64%) Amazon (35%), and Caatinga (1%). This work aimed to carry out a study of Eumorpha inventory with a taxonomic focus on three complexes of species occurring in Maranhão: Eumorpha anchemolus (Cramer, 1779), Eumorpha analis (Rothschild & Jordan, 1903) and Eumorpha obliquus (Rothschild & Jordan, 1903). We analyzed 194 specimens belonging to 13 species, seven of which are representatives of the examined complexes. The specimens studied come from 13 municipalities in the State, seven from the Cerrado biome, and six from the Amazon biome. This study contributed to the knowledge of the Eumorpha fauna and demonstrated that it is still underestimated throughout the Brazilian territory. Following this work the number of species has increased significantly for the Maranhão State. Moreover, our work showed that the identification carried out only by the external morphology of habitus is not efficient for the analyzed complexes of species. This present article also demonstrates that the use of genitalia characters is a good approach to separate species within the groups.